Cybersecurity training in control systems using real equipment*. Issue 1 (July 2017) - Domínguez, Manuel; Prada, Miguel A.; Reguera, Perfecto; Fuertes, Juan J.; Alonso, Serafín; Morán, Antonio
Abstract: The relevance of cybersecurity in the field of critical infrastructures has been reinforced in the last years, as a result of the increased number of incidents. The European Union has developed policies oriented to promote research and education in security and critical infrastructure protection. It is widely recognized that there is a shortage of qualified cybersecurity professionals due to the increasing demand. The situation is even more serious in the area of cybersecurity of critical infrastructures, due to the special characteristics of the control and monitoring systems needed for their operation. Furthermore, there is a knowledge gap between the industrial control experts, who generally have not received training in computer security, and the cybersecurity experts, who ignore the operation of industrial control systems. It is therefore necessary to create educational environments that support training and research oriented to bridge this gap without. For that reason, this paper presents a Laboratory of Critical Infrastructures Cybersecurity (CICLab) that is flexible enough to create different settings that simulate real situations on the critical infrastructure control systems. For that purpose, the laboratory includes different field, control and monitoring technologies that are widely used in four sectors: industry, energy management, building management and smart cities. Some educational activities are presented in the framework of this laboratory.